Analisis Kinerja Pengelola Data Kampung Keluarga Berkualitas (Kampung KB) Di Kota Prabumulih Tahun 2023 - Nur'Isyatur Rodiyah; Arie Wahyudi,; Chairil Zaman (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2023)
Kampung Keluarga Berkualitas are regional units at the village or sub-district level or equivalent with certain criteria where there is integration of the Bangga Kencana Program and Development Programs of other related sectors in an effort to improve the quality of life for families and communities. This study aims to analyze the performance of the data manager for Kampung Keluarga Berkualitas in Prabumulih City in 2023. The research design used is an analytic survey with a cross-sectional method involving 43 data managers for KB Villages in Prabumulih City. Collecting research data using a questionnaire. Analysis in research using the chi square test. The results showed that motivation (p Value 0.004, OR 9.524), workload (p Value 0.002, OR 18,000), and leadership supervision (p Value 0.045, OR 11.625) have a relationship with the performance of data managers. It is hoped that the role of the leadership will be effective in providing direction, guidance, instructions and conducting evaluations related to the implementation of tasks and work, so that conduciveness can be realized in the workplace, making Standard Operating Procedures (SOP) specifically for Recording and Reporting of KB Village Data and making On the Job Training so that the main tasks and functions of the KB Village data manager are not assigned to one person, it is necessary to increase and update the leadership supervision program, the effectiveness and implementation of supervision, follow-up on the implementation of supervision in order to increase the efficiency and effectiveness of the performance of the KB Village data manager and have an impact on the work results produced.